Correlation coefficient calculations for MIMO antenna systems: a comparative study. Issue 10 (4th September 2017) - Sharawi, Mohammad S.; Hassan, Abdelmoniem T.; Khan, Muhammad U.
Abstract : The correlation coefficient ( ρ ) is an important metric for the evaluation of multiple-input–multiple-output (MIMO) antenna systems because it describes the relationship between the channels in a particular propagation environment. Highly correlated channels will degrade the MIMO system performance. Various methods to calculate ρ are analyzed in this work using three different types of antennas with different efficiencies and radiating properties. While the field-based method for finding ρ gives the most accurate results and should be used all the time. It is independent of antenna efficiency. The the S-parameter-based method might give reasonable results only when the antenna efficiency is very high and the patterns are separated in space, but in most cases, it underestimates ρ values and thus is not a reliable method and should be avoided. Incorporating the antenna efficiency can improve the ρ estimates using the S-parameters method under some specific conditions. The equivalent circuit method provides reasonable results for symmetric antenna structures only, and is the most complex in formulation. As part of the evaluation, two existing methods incorporating the radiation efficiency of the antennas are generalized to N-ports for the first time. Although less accurate than the field-based method, these extensions allow the evaluation of ρ for N-port antennas using only the radiation efficiency and the S-parameters of the antenna. The effect of the beam tilts on ρ estimation is investigated for the first time.